Theoretical Fundamentals of Extensive Reading for Increasing Language Learners’ Proficiency - Piantzi, Leticia; Castillo, Maria; Tapia, Rebeca (CIEX JOURNAL, 2017)
This paper reports on the theoretical fundamentals of the benefits of the implementation of an Extensive Reading program at tertiary level. The main aim of this paper is to analyze the benefits of this approach to increase learners’ proficiency which can also be an example of how teachers can help language learners improve their proficiency when learning a language.